Linguistic picture of the world in the poetry of M. Kopeev - ABDULLAYEVA, K.M; TRUSHEV, A.K; ERGALIEV, K.S; ERLANOVA, A.E (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The goal of the research was to explore the linguistic picture of the world in the works of M. Zh. Kopeev. The main research methods were description, lexical and semantic, linguistic and textological, functional and cognitive, comparative, and stylistic analysis. The research results showed that the linguistic picture of the world and the experience of people living in this society are unique, since the life experience of each nation has its own specifics. Therefore, their conceptual consciousness builds a unique linguistic picture of the world, which results in the formation of the national identity.RESUMEN El objetivo de la investigación fue explorar la imagen lingüística del mundo en las obras de M. Zh. Kopeev. Los principales métodos de investigación fueron descripción, análisis léxico y semántico, lingüístico y textológico, funcional y cognitivo, comparativo y estilístico. Los resultados de la investigación mostraron que la imagen lingüística del mundo y la experiencia de las personas que viven en esta sociedad son únicas, ya que la experiencia de vida de cada nación tiene sus propios detalles. Por lo tanto, su conciencia conceptual construye una imagen lingüística única del mundo, que resulta en la formación de la identidad nacional.